Artificial intelligence as a better constraint against war - Lim, Nicholas Ding Feng (Nanyang Technological University, 2024)
In this paper, the author explores the potential application of Artificial Intelligence to decision-making in war, as a means of constraining it. Such emerging technology will only become more prominent and should be evaluated thoroughly. The paper first discusses the principles of jus ad bellum and jus in bello from just war theory. While intended to reduce the harm of war, the theory’s claim weakens our intuition about morality. The author also discusses issues faced by human decision-makers when considering how past costs should affect subsequent decisions. The author put forward the impartiality feature of such technology, taking in collective considerations as the key difference in reducing the harms of war. Artificial Intelligence in decision-making represents an opportunity to leverage in the ethical conduct of war. It has the potential as the next step of development in just war theory, seeking to minimize harm as the primary goal.